Artistic architectonics of human behavioral models in boundary situations and conditions: On the material of analysis of D. Brown’s novels «Angels and Demons» and M. Kidruk «Where there is no God» - Yehorova, Yulia; Mazhara, Nataliia; Khomchak Оlena; Akulova, Nadiia; Ohulchanska, Oksana (Linguistics and Culture Review, 2021)
The article is devoted to one aspect of the problem of reproduction of boundaries and states in a literary text, in particular the study of artistic architecture of human behavioral models in boundary situations and states. On the basis of philosophical and psychological works, the structural elements of such a model were identified. In invariant form, it consists of three main constructs, which are topos of limited rationality, compensatory satisfaction, awareness of potential meaning. Variant forms of architectonics of behavioral models in boundary situations and states may lose their individual components or differ in certain artistic and semantic nuances. The artistic architecture of the behavioral models of the characters in the article is studied on the material of the novels Dan Brown «Angels and Demons» and M. Kidruk «Where there is no God». There are similar approaches of the authors to the structuring of images-characters who are in borderline situations, and in both works revealed both invariant and variant forms of these structures. The invariant behavioral models of the characters in D. Brown’s novel «Angels and Demons» are mostly represented by images of lonely, individual figures (Carlo Ventresca, Pope Francis and Maximilian Kohler)